Susceptibilities of anaerobic bacteria to cefoperazone and other antibiotics. - Kaye, D (1980)
Two hundred fifty clinical isolates of anaerobic bacteria were tested for suceptibility to cefoperazone, cefamandole, cefoxitin, carbenicillin, clindamycin, and chloramphenicol. Anaerobic gram-positive cocci were susceptible to all of the antibiotics tested. Clindamycin was the most active agent against Bacteroides species, followed by chloramphenicol and then cefoxitin. Cefoperazone was less active than cefoxitin and equal in activity to carbenicillin. Cefamandole was the least active antibiotic against Bacteroides. B. distasonis, B. vulgatus, B. thetaiotaomicron, and B. ovatus were more resistant to the antibiotics than B. melaninogenicus, B. oralis, or B. bivius. Clindamycin was the most active agent against Clostridium species, followed by chloramphenicol; the three cephalosporins and carbenicillin were about equal in activity. Clindamycin was the most active antibiotic against Fusobacterium species, followed by chloramphenicol, carbenicillin, and cefoperazone (which were about equally active) and then cefamandole.